Regulatory identification of BPA as an endocrine disruptor: Context and methodology. (5th November 2018) - Beausoleil, Claire; Emond, Claude; Cravedi, Jean-Pierre; Antignac, Jean-Philippe; Applanat, Martine; Appenzeller, Brice R.; Beaudouin, Remy; Belzunces, Luc P.; Canivenc-Lavier, Marie-Chantal; Chevalier, Nicolas; Chevrier, Cécile; Elefant, Elisabeth; et al.
Abstract: BPA is one of the most investigated substances for its endocrine disruptor (ED) properties and it is at the same time in the center of many ED-related controversies. The analysis on how BPA fits to the regulatory identification as an ED is a challenge in terms of methodology. It is also a great opportunity to test the regulatory framework with a uniquely data-rich substance and learn valuable lessons for future cases. From this extensive database, it was considered important to engage in a detailed analysis so as to provide specific and strong evidences of ED while reflecting accurately the complexity of the response as well the multiplicity of adverse effects. An appropriate delineation of the scope of the analysis was therefore critical. Four effects namely, alterations of estrous cyclicity, mammary gland development, brain development and memory function, and metabolism, were considered to provide solid evidence of ED-mediated effects of BPA. Highlights: BPA is an ubiquitous substance due to its multiple and large uses. BPA is closely associated with ongoing controversies related to ED. Regulation of ED is in its early stages and requires a high level of evidence. Several ED-mediated effects of BPA achieve these requirements.